2018
DOI: 10.18203/2319-2003.ijbcp20181180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin on the severity and outcomes of ischemic stroke

Abstract: Background: Stroke is the third most common cause of death in the United States and the most commonly diagnosed neurological disorder. About 750,000 strokes occur annually in the United States and about 150,000 people die as a result of stroke. The aim of this study was evaluation of the effect of Metformin on complication of ischemic strokes.Methods: In this randomized, double-blind clinical trial study, 100 patients with ischemic stroke will be assigned randomly into two groups A and B. The National Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Post-stroke, chronic metformin treatment has suppressed the expression of 'M1'-associated genes (CD32, IL1b, CD16) and enhanced the expression of 'M2'-associated genes (CD206, Arg1) [58]. A clinical trial in patients with ischaemic stroke showed a significant decrease in NIHSS score in patients who were given metformin [117].…”
Section: Metforminmentioning
confidence: 99%
“…Post-stroke, chronic metformin treatment has suppressed the expression of 'M1'-associated genes (CD32, IL1b, CD16) and enhanced the expression of 'M2'-associated genes (CD206, Arg1) [58]. A clinical trial in patients with ischaemic stroke showed a significant decrease in NIHSS score in patients who were given metformin [117].…”
Section: Metforminmentioning
confidence: 99%